Developing Sustainable Careers Across the Lifespan European Social Fund Network on 'Career and AGE (Age, Generations, Experience) - De Vos, Ans.; Dujardin, Jean-Marie; Gielens, Tim; Meyers, Caroline; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book offers insights into facilitating sustainable careers through the study of a wide interdisciplinary range of policy investigations and assessment of ongoing practices in the field. By assessing and comparing the transferability of policies and good practices between firms in ten countries and regions of the European Union this book considers the development of sustainable careers across the lifespan at the levels of individuals, organizations and systems. This book is the culmination of a research project from the international European Social Fund network on 'Career and Age, Generation, Experience(AGE)'. It discusses and offers observations on key concerns at the European level: How to make people work longer, remain employable, develop sustainable competencies ? How to adapt the work environment and human resource management policies at employer's level ? And finally, how can public authorities take measures and incentives to support sustainable careers for individuals?
Chapter 1. Conceptual framework for sustainable careers -- Chapter 2. Description of relevant good practices at multiple levels -- Chapter 3. Context & Transfer issues: how can good practices be transferred? -- Chapter 4. Six recommendations for facilitating sustainable careers -- Chapter 5. How can you get started when implementing sustainable careers ? -- Chapter 6. Sustainable competences and career competencies: how to put the individual in the driver's seat? -- Chapter 7. Final Conclusions.
Keywords: Applied psychology; Personnel management; Adult education